Changes in Romantic Competence and Career Adaptability Among Emerging Adults in Psychotherapy. (October 2016) - Atzil-Slonim, Dana; Reshef, Muli; Berman, Emmy; Peri, Tuvia; Shulman, Shmuel
While studies indicate that a growing number of emerging adults have difficulty meeting developmental challenges and, as a consequence, experience distress, the extent to which psychotherapy can help emerging adult clients cope with developmental tasks remains unexplored. This study examined the extent to which two core developmental capabilities of emerging adults—romantic competence and career adaptability—change during psychotherapy and the association between these changes and symptom change. Forty-six clients aged 21–31 (26 females; 56%) completed outcome measures and interviews regarding their romantic competence and career adaptability at the beginning and the end of psychodynamic psychotherapy. The mean duration of treatment was 26 sessions ( SD = 6.88). Findings indicated that romantic competence and career adaptability increased significantly throughout treatment while symptoms decreased. Change in romantic competence was associated with change in symptoms. The findings suggest that therapy could be helpful in the pursuit of the core developmental tasks; and that improvement in romantic competence is associated with symptom relief.